Atrophy of hip abductor muscles is related to clinical severity in a hip osteoarthritis population. Issue 4 (8th March 2018) - Zacharias, Anita; Green, Rodney A.; Semciw, Adam; English, Daniel J.; Kapakoulakis, Theo; Pizzari, Tania
Abstract : Osteoarthritis mainly affects weight‐bearing joints such as the hip and knee and is the most common form of arthritis. Greater muscle atrophy with fatty infiltration of gluteal muscles and decreased hip abduction strength has previously been identified with increasing severity of radiological hip OA. However, it is well documented that radiographic findings of OA do not always correlate with clinical severity. The aim of this secondary analysis was to examine whether atrophy and strength of gluteus maximus (GMax), medius (GMed), minimus (GMin), and tensor fascia lata (TFL) is associated with the clinical severity of OA. Twenty participants with unilateral hip OA and 20 age‐ and sex‐matched asymptomatic controls were classified on the basis of clinical severity (mild, moderate‐severe and asymptomatic groups) using the Oxford hip score. Muscle volumes of GMax, GMed, GMin, and TFL were determined using magnetic resonance imaging and expressed as asymmetry between limbs. A hand‐held dynamometer was used to identify hip rotation and abduction strength. Regression analyzes were used to identify the association between muscle asymmetry and patient‐reported severity of hip OA. Both symptomatic groups (mild and moderate‐severe) demonstrated significant asymmetry in GMax ( P < 0.01) and GMin ( P < 0.01). GMed asymmetry was associated with only the moderate‐severe symptomatic group. Hip abduction strength was reduced in both symptomatic groups. Gluteal muscle atrophy was associated with the clinical severity of OA. Clinical severity could be a useful tool for clinicians interpreting likely gluteal muscle changes and planning rehabilitation strategies for hip OA patients. Clin. Anat. 31:507–513, 2018. © 2018 Wiley Periodicals, Inc.